2022
DOI: 10.3389/fmed.2022.927607
|View full text |Cite
|
Sign up to set email alerts
|

Yifei Sanjie Formula Treats Chronic Obstructive Pulmonary Disease by Remodeling Pulmonary Microbiota

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the most common pulmonary diseases. Evidence suggests that dysbiosis of pulmonary microbiota leads to the COPD pathological process. Yifei Sanjie Formula (YS) is widely used to treat diseases in respiratory systems, yet little is known about its mechanisms. In the present study, we first established the fingerprint of YS as the background for UHPLC-QTOF-MS. Components were detected, including alkaloids, amino acid derivatives, phenylpropanoids, flavonoids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown that YFSJ is a widely used Chinese herbal medicine for treating lung related diseases. 7,8,12,13 The YFSJ formula, a TCM, has been shown to have a broad pharmacological action against lung diseases. It has been found to lower inflammatory responses and reduce lung damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have shown that YFSJ is a widely used Chinese herbal medicine for treating lung related diseases. 7,8,12,13 The YFSJ formula, a TCM, has been shown to have a broad pharmacological action against lung diseases. It has been found to lower inflammatory responses and reduce lung damage.…”
Section: Discussionmentioning
confidence: 99%
“…TCM has an extensive track record of effectively treating lung cancer with minimal adverse effects and increased patient survival, 43 which justifies further comprehensive investigation. Numerous studies have shown that YFSJ is a widely used Chinese herbal medicine for treating lung related diseases 7,8,12,13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, Ralstonia is an important inflammatory factor in the intestine. [27][28][29][30][31][32] The study further showed that the abundance of Pseudomonas and Ralstonia in the R group was significantly higher than in the T group (p<0.05). We speculate that the composition of tilapia intestinal flora in the rice-fish symbiosis mode is more conducive to fish health.…”
Section: Discussionmentioning
confidence: 99%